2005
DOI: 10.1097/01.brs.0000153404.62017.75
|View full text |Cite
|
Sign up to set email alerts
|

The Success of Thoracoscopic Anterior Fusion in a Consecutive Series of 112 Pediatric Spinal Deformity Cases

Abstract: Thoracoscopic anterior release and fusion of the thoracic spine is a safe and effective procedure when combined with posterior instrumentation and fusion. The primary goal of increasing the flexibility of a rigid spine and achieving a solid arthrodesis occurred in the vast majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 13 publications
(14 reference statements)
1
36
0
2
Order By: Relevance
“…53,77 In addition, VATS has been used to place anterior instrumentation for correction of thoracic and thoracolumbar AIS. 2,16,21,41,42,54,56,58,73,81 Retrospective reviews have suggested that thoracoscopic spinal instrumentation compares favorably with anterior instrumentation through thoracotomy 16,54 and with posterior fusion. 41,81 Although a limited number of groups demonstrate acceptable results using VATS for the surgical treatment of AIS, this approach is not widely used, probably due in part to the relatively steep learning curve, 43,58,81 limitations in curve correction, 2,21,36,58 and the high incidence of pulmonary complications.…”
Section: Neurosurg Focus / Volume 25 / August 2008mentioning
confidence: 99%
See 1 more Smart Citation
“…53,77 In addition, VATS has been used to place anterior instrumentation for correction of thoracic and thoracolumbar AIS. 2,16,21,41,42,54,56,58,73,81 Retrospective reviews have suggested that thoracoscopic spinal instrumentation compares favorably with anterior instrumentation through thoracotomy 16,54 and with posterior fusion. 41,81 Although a limited number of groups demonstrate acceptable results using VATS for the surgical treatment of AIS, this approach is not widely used, probably due in part to the relatively steep learning curve, 43,58,81 limitations in curve correction, 2,21,36,58 and the high incidence of pulmonary complications.…”
Section: Neurosurg Focus / Volume 25 / August 2008mentioning
confidence: 99%
“…41,81 Although a limited number of groups demonstrate acceptable results using VATS for the surgical treatment of AIS, this approach is not widely used, probably due in part to the relatively steep learning curve, 43,58,81 limitations in curve correction, 2,21,36,58 and the high incidence of pulmonary complications. 56,58,73 Development of a minimally invasive approach for the treatment of AIS that applies more conventional skills and avoids entering the chest would be a significant advancement in the surgical treatment of this deformity. Lateral interbody discectomy and fusion systems have been developed for the lumbar spine, including DLIF (Medtronic) and XLIF (NuVasive).…”
Section: Neurosurg Focus / Volume 25 / August 2008mentioning
confidence: 99%
“…23 Thoracoscope-assisted procedures for spinal deformity are performed for anterior releases to increase both the flexibility of the spine and the fusion surface area with anterior intervertebral fusions. 25,26,40 Advantages of thoracoscopic surgery for spinal deformity include decreased surgical trauma, scarring, postoperative pain, and perioperative morbidity. In addition, compared with posterior approaches, anterior procedures in spinal deformity surgeries can reduce the number of fusion segments required to achieve curve correction.…”
Section: Spinal Deformitymentioning
confidence: 99%
“…2 It occurs as a postoperative complication after various surgeries involving structures in the neck and thorax. [39][40][41][42][43][44] Other surgeries that can be complicated by chylothorax in children include those for treatment of scoliosis, [45][46][47][48] vascular rings, 49,50 and diaphragmatic hernia. 51 In children, the reported incidence of chylothorax after cardiothoracic surgery is between 0.85% and 6.6%.…”
Section: Causes Of Chylothoraxmentioning
confidence: 99%